The Effect of Zakat Institution System and Government Support on Intention to Pay Zakat: Knowledge as A Moderating Variable - Sudarsono, Heri; Nugrohowati, Rindang Nuri Isnaini; Tumewang, Yunice Karina (EQUILIBRIUM, 2021)
This study aims to determine the effect of attitudes, subjective norms, zakat institution system and government support in influencing the interest of the government and private officers to pay zakat. This study also aims to determine the extent of muzakki’s knowledge of zakat in improving attitudes, subjective norms, zakat institutional systems and government support in the interest of the government and private officers to pay zakat. Respondents in this study are 402 respondents consisting of 154 government officers and 248 private officers who live in 6 big cities in Java, such as Jakarta, Serang, Bandung, Semarang, Yogyakarta and Surabaya. This research uses the Partial-Least-Square Structural Equation Modeling (PLS-SEM) analysis technique with the Theory of Reasoned Action (TRA) model. The finding reveals that attitudes, subjective norms, zakat institutional system, and government support affect the government and private officers' interest in paying zakat. Meanwhile, knowledge as a moderating variable does not strengthen the influence of attitudes, zakat institutional systems and government support. Still, it reinforces the subjective norms of government and private officers in influencing intention to pay zakat. BAZNAS can collaborate with educational institutions, professional institutions, community institutions and utilize social networks to increase public knowledge about zakat. Hence, knowledge about zakat supports subjective norms and attitudes, zakat institutional system, and government support.